Electronically controlled constant rate of load tensile machine - Naval Air Experimental Station; United States. Navy (1949)
General view of an electronically-controlled constant rate of load tensile machine used in the Naval Air Experimental Station's Physical Properties Laboratory. Tensile machines are commonly used to subject materials samples to controlled tension until failure, a process known as tensile or tension testing. In materials science, such testing is used to select a material for an application, for quality control, and to predict how a material will react under other types of forces. At the Physical Properties Laboratory, this machine was likely used to evaluate rubber and rubber-like materials. This photograph was included in a 1949 Naval Air Experimental Station report on compounding rubber.
Keywords: Aerospace Research Laboratories (U.S.); Quality control; Materials science; Naval Research Laboratory (U.S.); Machinery